Homocysteine and Insulin Resistance among Women with Polycystic Ovary Syndrome: Homosistein dan Resistensi Insulin pada Wanita dengan Sindrom Ovarium Polikistik - Wahid, Hayder S. Abdul; Ajlan, Salman K.; Kadhim, Amal Abdul Mahdi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Polycystic ovary syndrome (PCOS) is the most common endocrinopathy in women of reproductive age, often associated with obesity, insulin resistance (IR), and metabolic dysfunction. Specific Background: Emerging evidence suggests that hyperhomocysteinemia (HHcy) may contribute to the metabolic and cardiovascular complications of PCOS, yet its relationship with IR and β-cell function remains unclear. Knowledge Gap: While previous studies have linked homocysteine (Hcy) to insulin sensitivity, limited data exist regarding its direct correlation with β-cell activity in PCOS patients. Aim: This study aimed to evaluate the correlation of Hcy levels with IR and β-cell function among women diagnosed with PCOS. Results: In a case-control design including 100 PCOS patients and 100 controls, women with PCOS exhibited significantly higher Hcy, fasting glucose, insulin, HOMA-IR, HOMA-B, testosterone, and HbA1c levels. Hcy correlated positively with HOMA-IR, fasting glucose, insulin, HbA1c, and testosterone, but showed no significant association with β-cell function. Novelty: This study highlights Hcy as a strong metabolic marker linked to IR and glycemic dysregulation, independent of β-cell activity in PCOS. Implications: These findings suggest that elevated Hcy may exacerbate the risk of type 2 diabetes, metabolic syndrome, and cardiovascular disease in women with PCOS, underscoring the need for early metabolic monitoring and intervention.Highlight : Strong correlation found between homocysteine and insulin resistance in PCOS women. Elevated insulin and glycaemic markers increase risk of T2D and related disorders. No significant correlation between homocysteine and β-cell function. Keywords : Polycystic Ovarian Syndrome, Homocysteine, Insulin Resistance, β-cell Function, Cardiovascular Disease